11β-HSD1 contributes to age-related metabolic decline in male mice. Issue 3 (7th October 2022) - Morgan, Stuart A; Gathercole, Laura L; Hassan-Smith, Zaki K; Tomlinson, Jeremy; Stewart, Paul M; Lavery, Gareth G
Abstract : The aged phenotype shares several metabolic similarities with that of circulatory glucocorticoid excess (Cushing's syndrome), including type 2 diabetes, obesity, hypertension, and myopathy. We hypothesise that local tissue generation of glucocorticoids by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), which converts 11-dehydrocorticosterone to active corticosterone in rodents (corticosterone to cortisol in man), plays a role in driving age-related chronic disease. In this study, we have examined the impact of ageing on glucocorticoid metabolism, insulin tolerance, adiposity, muscle strength, and blood pressure in both wildtype (WT) and transgenic male mice with a global deletion of 11β-HSD1 (11β-HSD1 −/− ) following 4 months high-fat feeding. We found that high fat-fed 11β-HSD1 −/− mice were protected from age-related glucose intolerance and hyperinsulinemia when compared to age/diet-matched WTs. By contrast, aged 11β-HSD1 −/− mice were not protected from the onset of sarcopenia observed in the aged WTs. Young 11β-HSD1 −/− mice were partially protected from diet-induced obesity; however, this partial protection was lost with age. Despite greater overall obesity, the aged 11β-HSD1 −/− animals stored fat in more metabolically safer adipose depots as compared to the aged WTs. Serum analysis revealed both WT and 11β-HSD1 −/− mice had an age-related increase in morning corticosterone. Surprisingly, 11β-HSD1 oxo-reductase activity in the liver and skeletal muscle was unchanged with age in WT mice and decreased in gonadal adipose tissue. These data suggest that deletion of 11β-HSD1 in high fat-fed, but not chow-fed, male mice protects from age-related insulin resistance and supports a metabolically favourable fat distribution.